Project to Develop an Interoperable Seafood Traceability Technology Architecture: Issues Brief. Issue 2 (19th January 2016) - Bhatt, Tejas; Cusack, Chris; Dent, Benjamin; Gooch, Martin; Jones, Dick; Newsome, Rosetta; Stitzinger, Jennie; Sylvia, Gil; Zhang, Jianrong
Abstract: The Interoperable Seafood Traceability Technology Architecture Issues Brief reflects the growing need to establish a global, secure, interoperable support system for seafood traceability. Establishing effective traceability systems relies on the development of a cohesive and consistent approach to the delivery of information technology capabilities and functions. The ability of business to utilize traceability for commercial gain is heavily influenced by the supply chain in which they operate. The Issues Brief describes factors associated with enterprise‐level traceability systems that will impact the design of technology architecture suited to enabling whole chain interoperable traceability. The Brief details why a technology architecture is required, what it means for industry in terms of benefits and opportunities, and how the architecture will translate into practical results. The current situation of many heterogeneous proprietary systems prevents global interoperable traceability from occurring. Utilizing primary research and lessons learned from other industries, the Brief details how the present situation can be addressed. This will enable computerized information systems to communicate syntactically by sharing standardized packages of data. The subsequent stage, semantic interoperability, is achieved by establishing a common language (ontology). The report concludes with a series of recommendations that industry can act upon to design a technology architecture suited to enabling effective global interoperable traceability.